Crown Rot of Abies balsamea var. phanerolepis Caused by Phytophthora cactorum in Virginia - Hong, C X (Plant disease, 2005)
In early July 2004, a severe crown rot of Canaan fir (Abies balsamea var. phanerolepis Fern.) was reported to the Virginia Cooperative Extension, Frederick County Office, and subsequently to the Virginia Tech Disease Clinic in Virginia Beach. One thousand five-year-old Canaan fir transplants (approximately 11 mm in caliper and 31 cm high) had been purchased from a tree nursery in Oregon and planted in the field in Frederick County, VA, in April of 2004. The field site had not been cultivated for 4 years after an apple orchard had been removed in 2000. By mid-May, needle browning had become serious, affecting the lower crown first. By August, transplants had suffered 40% mortality. Basal stems of affected plants were obviously discolored. Root and basal stem samples from several infected plants were then cultured on PARP-V8 agar on three different dates. Phytophthora sp. isolates were recovered from all stem samples but none from the roots. These isolates produced a large number of papillate sporangia that were caducous with short pedicels. Abundant oogonia with paragynous antheridia formed oospores directly on isolation plates within 7 days. The isolates were keyed as P. cactorum (2). This identification was confirmed using a single-strand-conformation polymorphism analysis of ribosomal DNA internal transcribed spacer (ITS)-1 (4). It appears that the source of inoculum was P. cactorum associated with the previous apple crop, since Canaan fir from the same transplant lot planted in a nearby field without a history of apples remained healthy. P. cactorum has been reported to cause root rot of noble fir (A. procera Rhedo), Pacific silver fir (A. amabilis (Dougl.) Forbes), and Shasta red fir (A. magnifica var. shastensis Lemm.) in the Pacific Northwest (3). It has also caused crown rot of Fraser fir (A. fraseri (Pursh) Poir.), noble fir, white fir (A. concolor (Gord. & Glend.) Lindl.), and balsam fir (A. balsamea (L.) Mill.) in Michigan (1). To our knowledge, this is the first report of P. cactorum attacking Canaan fir. Canaan fir currently is a recommended Christmas tree species for areas where Fraser fir does not do well due to root rot caused by Phytophthora cinnamomi. This study suggests that such a recommendation must be used with caution. Growing Canaan fir trees in P. cactorum-infested soil could result in devastating crop losses as reported in this note. References: (1) G. C. Adams, Jr. and A. Bielenin. Plant Dis. 72:79, 1988. (2) D. C. Erwin and O. K. Ribeiro. Phytophthora Diseases Worldwide. The American Phytopathological Society, St. Paul, MN, 1996. (3) P. B. Hamm and E. M. Hansen. Eur. J. For. Pathol. 12:167, 1982. (4) P. Kong et al. Fungal Genet. Biol. 39:238, 2003